1999
DOI: 10.1207/s15327558ijbm0604_3
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of cardiac events in hypertensive men related to adaptive behavior in stressful encounters

Abstract: The Serial Color Word Test was administered at baseline to 253 hypertensive men participating in the prospective cohort study of cardiovascular diseases "Men born in 1914" in Malmö, Sweden. This test of psychological adaptation to a stressful encounter was used to investigate whether susceptibility to stress moderates the risk of a cardiac event in association with hypertension. Adaptive behavior, as measured by test performance, can be categorized in two dimensions. The regression dimension refers to linear c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…A cumulative-dissociative behavior pattern is described as "an initially tight control that, as a result of repeated efforts and failures to find successful strategies to master the conflict, is exhausted by the end of the test." An earlier study of the same cohort 38 found that this cumulativedissociative adaptation to stress was also associated with increased risk of cardiac events. Thus, healthy men with elevated cardiovascular reactions to stress and hypertensive men who adapt poorly to stressful situations may be more vulnerable to stroke.…”
Section: Editorial Comment Cardiovascular and Behavioral Reactions Tomentioning
confidence: 83%
“…A cumulative-dissociative behavior pattern is described as "an initially tight control that, as a result of repeated efforts and failures to find successful strategies to master the conflict, is exhausted by the end of the test." An earlier study of the same cohort 38 found that this cumulativedissociative adaptation to stress was also associated with increased risk of cardiac events. Thus, healthy men with elevated cardiovascular reactions to stress and hypertensive men who adapt poorly to stressful situations may be more vulnerable to stroke.…”
Section: Editorial Comment Cardiovascular and Behavioral Reactions Tomentioning
confidence: 83%
“…Its prognostic value in 'Men born in 1914' has, however, been shown in previous studies where the dimension Variability was associated with the incidence of a future cardiac event in hypertensive men [13] and the Regression with stroke incidence, also in hypertensive men [14]. In addition, the serial CWT has been validated against psychiatric syndromes and diagnoses in clinical settings [15], and it has discriminated between different psychosomatic disorders [22,40] and between various groups with and without clinical symptoms [41].…”
Section: Discussionmentioning
confidence: 97%
“…The fourth pattern, the Cumulativedissociative, shows increasing time consumption from the first subtest until the last, combined with intermittently increasing and decreasing time consumption in each subtest. More information on, and graphic illustrations of, the adaptive patterns have been given in detail [8,13,22].…”
Section: Administration and Scoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychosocial factors that can be considered chronic stressors include low socioeconomic status, poor social support, and various situations in which individuals are exposed to stress [6]. Unique behavioural factors associated with stressful events have also been assumed to be risk factors linked to myocardial infarction (MI) and increased risk of death after such an event [12,13]. …”
Section: Introductionmentioning
confidence: 99%